2023
DOI: 10.3390/nu15030616
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Condiments, Seasonings, and Bouillon Cubes to Deliver Essential Micronutrients in Asia: Scenario Analyses of Iodine and Iron Fortification

Abstract: Micronutrient deficiencies are still highly prevalent in Asia. Fortification of cooking aids, such as condiments (fish and soy sauces), seasonings, and bouillon cubes, may be an additional strategy to improve micronutrient intake. The current study evaluated the potential impact of iodine and iron fortification of cooking aids on micronutrient intake in Asian countries. A systematic literature search was performed to collect consumption data from different countries in Asia. Data from 18 studies in nine Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The regulation of iron homeostasis, encompassing absorption, utilization, storage, and excretion, is a tightly controlled process [58,59]. Iron plays a crucial role in the formation of hemoglobin and myoglobin, which are essential for the transportation of oxygen in the body [60,61]. This function is vital for the maintenance of tissue oxygenation and cellular energy production [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of iron homeostasis, encompassing absorption, utilization, storage, and excretion, is a tightly controlled process [58,59]. Iron plays a crucial role in the formation of hemoglobin and myoglobin, which are essential for the transportation of oxygen in the body [60,61]. This function is vital for the maintenance of tissue oxygenation and cellular energy production [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not model the impact of the standards for micronutrients for the US population, the potential impact of fortification of bouillons and seasonings with iron and iodine was evaluated in another study based on intake data of different Asian countries. The study showed that fortifying bouillons & seasonings with iron and iodine at levels in line with the PNS can help to increase the intake with approximately 33% of the RDA ( 37 ).…”
Section: Discussionmentioning
confidence: 99%